2023
DOI: 10.3390/ph16020274
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids-Mediated Regulation of Molecular Targets in Ovarian Cancer: Current Understanding and Future Perspectives

Abstract: Cancer is a global health concern with a dynamic rise in occurrence and one of the leading causes of mortality worldwide. Among different types of cancer, ovarian cancer (OC) is the seventh most diagnosed malignant tumor, while among the gynecological malignancies, it ranks third after cervical and uterine cancer and sadly bears the highest mortality and worst prognosis. First-line treatments have included a variety of cytotoxic and synthetic chemotherapeutic medicines, but they have not been particularly effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 165 publications
0
0
0
Order By: Relevance
“…Polyphenols, due to their natural origin, are generally believed to be non-toxic and safe. Data from clinical and preclinical studies demonstrated that the evaluated phenolic compounds were well tolerated, free of adverse effects and had a high safety profile [ 139 , 140 ]. However, this cannot be established as a rule.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Polyphenols, due to their natural origin, are generally believed to be non-toxic and safe. Data from clinical and preclinical studies demonstrated that the evaluated phenolic compounds were well tolerated, free of adverse effects and had a high safety profile [ 139 , 140 ]. However, this cannot be established as a rule.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Among the phenolic acids, gallic acid is recognized as the most prevalent hydroxybenzoic acid, being abundant both in natural sources (oak gallnuts/leaves/bark/acorns, pomegranate root bark, berry/tea leaves, many fruits and vegetables), as well as in processed beverages (red wine and green tea) [78][79][80]. Significant amounts of gallic acid were reported in oak galls, both in the case of extraction with a conventional technique (291 mg/g dry weight (dw)) [8] and with ultrasonic-probe assisted extraction (UPAE) (130.76 mg/g dw) [43].…”
Section: Phenolic Compounds Of Quercus Sp Gallsmentioning
confidence: 99%
“…Ellagic acid is a dimeric gallic acid derivative, widely present in fruits (pomegranate, mango, grapes), berries (blackberry, raspberry, blueberry, cranberry, and strawberry), nuts (walnuts, pecans, chestnuts, almonds), seeds, dry fruits, and some types of honey, but also in herbs, roots, and alcoholic beverages matured in oak wooden barrels [78,81]. In oak galls, the highest amounts of ellagic acid (261,997.718 and 187,696.132 µg/g dw, respectively) were reported in two studies by Kılınçarslan Aksoy et al [10,40].…”
Section: Phenolic Compounds Of Quercus Sp Gallsmentioning
confidence: 99%
See 1 more Smart Citation